The Relationship Of Postpartum Mother's Characteristics With Infant Massage Knowledge At Rs Reksodiwiryo Padang - Syafputri, Trymaya; Kurnia, Deva (Alifah Health Science Symposium Proceeding, 2023)
This study aims to determine the relationship between postpartum maternal characteristics and knowledge of infant massage at Reksodiwiryo Hospital, Padang.This research uses an analytical survey method with a cross-sectional approach. The respondents studied were postpartum mothers who were being treated at Reksodiwiryo Hospital in Padang and 40 respondents were obtained. The data was processed manually using the Chi Square test with a confidence level of 95%. The mother age group of 20-30 years had good knowledge at 84.2%, while mothers aged >30 years had less knowledge at 31.2%. Respondents with 11-12 years of education had 100% good knowledge, while those with 7-9 years of education had less than 38.5%. Parity II mothers had good knowledge of 94.5%, and parity I mothers had poor knowledge of 50%. There is no relationship between age and maternal knowledge (X2 = 1.211 p > from α 0.05), there is no relationship between education and postpartum maternal knowledge (X2 = 5.97 p > from α 0.05), but there is a significant relationship significant between parity and maternal knowledge (X2 = 9.494 p < of α 0.05). Statistically there is a relationship between parity I and parity II of postpartum mothers and knowledge of baby massage. Meanwhile, between ages 20-30 years and ages > 30 years and years of education 7-9 years and 11-12 years and knowledge of baby massage, there was no significant relationship.